Soliton solutions of the complex Ginzburg-Landau Equation - Yousif Rasheed, Faisal Salah; Abdul Aziz, Zainal (Faculty of Science, 2009)

(untitled)
The function transformed method is applied to an n-dimensional complex Ginzburg-Landau equation (CGLE), which is being transformed to physically significant well known nonlinear waves equations depending only on the function ?, and these equations can be exactly solved. The solution of these equations in is shown to lead to a general soliton solution of the CGLE